Comparative epidemiological analysis of tumors of the digestive system in dogs and cats - Araújo, Diana; da Silva, Gabriela Fernanades; Carvalho, Fátima; Vale, Nuno; Niza-Ribeiro, João; Ribeiro, Ana Isabel; Amorim, Irina; Pinello, Katia (Frontiers in Veterinary Science, 2025)
IntroductionGastrointestinal (GI) disorders are a leading reason for veterinary care.MethodsThis study analyzed digestive tract tumors in dogs and cats in Portugal using data from the Vet-OncoNet database, focusing on frequency, risk factors, and geographic distribution.Results and discussionA total of 1,213 cases were included: 617 dogs (50.9%) and 596 cats (49.1%), with a higher proportion of males (54.9%) than females (45.1%). The most affected organs overall were the small intestine (26.5%) and liver/intrahepatic bile ducts (16.7%). In dogs, tumors were mainly located in the liver and bile ducts (25.8%), rectum (19.0%), small intestine (13.8%), and stomach (8.9%). In cats, the small intestine was the primary site (39.6%), followed by liver/bile ducts (7.4%), stomach (7.3%), and colon (3.5%). Lymphoma was the most common tumor type in both species (42.2%), followed by adenocarcinoma (19.0%). Among dogs, mixed breeds, Labrador Retrievers, German Shepherds, and French Bulldogs were most affected. In cats, Common European, mixed-breed, and Norwegian Forest cats predominated. The incidence rate (IR) of digestive tumors was 3.5 times higher in cats than dogs. Male cats had a 1.5 times higher IR than females. Cats also had 16 times higher risk for GI lymphoma and twice the risk for adenocarcinoma compared to dogs. Certain dog breeds, including West Highland White Terrier, Siberian Husky, and Golden Retriever, showed higher tumor incidence. Spatial analysis revealed concentration in urbanized areas, particularly around Porto and Lisbon. Conclusion: These findings highlight notable species-specific differences in digestive tract tumors, suggesting distinct genetic predispositions and possible environmental influences.